Vitreous Hemorrhage as the Presenting Sign of Idiopathic Intracranial Hypertension - Amir R. Vosoughi; Jonathan A. Micieli (Case Reports in Ophthalmology, 2022)
Vitreous hemorrhage from papilledema has rarely been reported in the literature. It likely results from an acute increase in intracranial pressure leading to venous compression and rupture. We herein describe a 32-year-old woman who presented with flashes and floaters and was found to have vitreous hemorrhage due to idiopathic intracranial hypertension (IIH). She was treated with acetazolamide, and at 6-month follow-up, regained normal visual function with resolution of optic nerve swelling and hemorrhage. Our case demonstrates that patients with IIH may rarely present with floaters due to vitreous hemorrhage from papilledema. This case also re-iterates that the extent and presence of vitreous and optic disc hemorrhage likely does not confer a prognostic value in patients with papilledema.